USING KANO TWO DIMENSIONAL SERVICE QUALITY CLASSIFICATION AND CHARACTERISTIC ANALYSIS FROM THE PERSPECTIVE OF HOTELS’ CLIENTS OF ORADEA - BAN, Olimpia Iuliana; MESTER, Ioana T (Revista de turism - studii și cercetări în turism, 2014)
Kano's two-dimensional quality model is one of the best known and most used direct methods, in service quality appreciation. The main purpose of this paper is to apply and testing a two-dimensional model proposed by Noriaki Kano, in a real situation of four hotels from Oradea. The first part of the paper presents, the stages needed to build the Kano model, in the context of researches regarding the degree of satisfaction of the consumer of touristic services and the advantages of using this method. The second part of the paper describes a market research, through questionnaire, among the 125 clients of four hotels with over 50 rooms and located in key areas for the urban tourism. The results obtained show the degree of global satisfaction of the clients surveyed and allow the framing of the quality attributes into the three main categories(plus one) suggested by Kano. Applying Kano`s model we have a position of consumers face tinting of the quality characteristics, this is impossible in classical quality assessment services.